Interaction of Depot Medroxyprogesterone Acetate and Tenofovir Disoproxil Fumarate/Emtricitabine on Peripheral Blood Mononuclear Cells and Cervical Tissue Susceptibility to HIV Infection and Pharmacokinetics. (1st January 2023) - Coleman, Jenell S.; Diniz, Clarissa P.; Fuchs, Edward J.; Marzinke, Mark A.; Aung, Wutyi; Bakshi, Rahul P.; Farzadegan, Homayoon; Bream, Jay H.; Nilles, Tricia L.; Hudson, Sherry; Bumpus, Namandjé N.; Schwartz, George J.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Depot medroxyprogesterone acetate (DMPA) is a widely used contraceptive method. HIV pre-exposure prophylaxis with emtricitabine and tenofovir disoproxil fumarate (F/TDF) is highly effective in reducing HIV acquisition in women. We sought to determine the impact of DMPA on F/TDF pharmacokinetics and pharmacodynamics. Methods: Twelve healthy premenopausal cisgender women were enrolled and each completed 4 sequential conditions: (1) baseline, (2) steady-state F/TDF alone, (3) steady-state F/TDF + DMPA, and (4) DMPA alone. Assessments included clinical, pharmacokinetic, viral infectivity (ex vivo challenge of peripheral blood mononuclear cells by X4- and R5-tropic green fluorescent protein pseudoviruses and cervical tissue by HIVBaL ), endocrine, immune cell phenotyping, and renal function. Results: Compared with baseline, F/TDF (± DMPA) significantly decreased both %R5- and X4-infected CD4 T cells and F/TDF + DMPA decreased cervical explant p24 (all P < 0.05). The %R5- and X4-infected CD4 T cells were higher during DMPA alone than during F/TDF periods and lower than baseline (not statistically significant). Cervical explant p24 fell between baseline and F/TDF values (not statistically significant). There were neither statistically significant differences in F/TDF pharmacokinetics, including total or renal clearance of either antiviral drug, nor changes in glomerular filtration rate with the addition of DMPA. There were few immune cell phenotypic differences across conditions. Conclusions: F/TDF decreased HIV infection in both challenge assays, whereas DMPA alone did not enhance HIV infection in either challenge assay. DMPA did not alter F/TDF pharmacokinetics or renal function.